Fifth-grade elementary school perception of STEM - T Trivena; A Widodo; W Sopandi; T Budiarti; Y Gumala (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to determine the early perception of fifth grade of students about STEM (Science Technology Engineering Mathematics). The method used in this research is descriptive-qualitative method with the participant amounted to 34 fifth graders in one of elementary school in Bandung city. The instrument used in this study is a questionnaire of students' perceptions about STEM which amounted to 49 items. The results of data analysis collected showed that the students' early perception of STEM was quite high with an average of 78%, which 66% in terms of interest, 63% in terms of difficulty, 80% in terms of ability, 69% in terms of readiness, 76% in terms of influence, 78% in terms of career and 75% in terms of benefit. This is because students' much interest in STEM subjects such as Science and Mathematics is much greater even though it has not become the main choice subject. Therefore, it is necessary to do further research related STEM implementation in learning process at elementary school which is to see student perception after applied this approach.